Design of an equilibrative nucleoside transporter subtype 1 inhibitor for pain relief - Nicholas J. Wright; Yutaka Matsuoka; Hyeri Park; Wei He; Caroline G. Webster; Kenta Furutani; Justin G. Fedor; Aidan McGinnis; Yiquan Zhao; Ouyang Chen; Sangsu Bang; Ping Fan; et al. (Nature Communications)
Abstract The current opioid crisis urgently calls for developing non-addictive pain medications. Progress has been slow, highlighting the need to uncover targets with unique mechanisms of action. Extracellular adenosine alleviates pain by activating the adenosine A1 receptor (A1R). However, efforts to develop A1R agonists have faced obstacles. The equilibrative nucleoside transporter subtype 1 (ENT1) plays a crucial role in regulating adenosine levels across cell membranes. We postulate that ENT1 inhibition may enhance extracellular adenosine levels, potentiating endogenous adenosine action at A1R and leading to analgesic effects. Here, we modify the ENT1 inhibitor dilazep based on its complex X-ray structure and show that this modified inhibitor reduces neuropathic and inflammatory pain in animal models while dilazep does not. Notably, our ENT1 inhibitor surpasses gabapentin in analgesic efficacy in a neuropathic pain model. Additionally, our inhibitor exhibits less cardiac side effect than dilazep via systemic administration and shows no side effects via local/intrathecal administration. ENT1 is colocalized with A1R in mouse and human dorsal root ganglia, and the analgesic effect of our inhibitor is linked to A1R. Our studies reveal ENT1 as a therapeutic target for analgesia, highlighting the promise of rationally designed ENT1 inhibitors for non-opioid pain medications.